Serum levels of erythropoietin and soluble transferrin receptor in the course of pregnancy in non beta thalassemic and beta thalassemic women - I Bianco; F Mastropietro; C D'Asero; B Graziani; P Piergrossi; M Mezzabotta; G Modiano (Haematologica, 2000)
BACKGROUND AND OBJECTIVES: In non-thalassaemic women serum erythropoietin (Epo) level increases during pregnancy, whereas that of soluble transferrin receptor (STFR) drops slightly in the first two trimesters to attain the original values in the third trimester. In this study the time-course of these two parameters was explored in b-thalassemic and non-b-thalassemic women, both pregnant and not. DESIGN AND METHODS: Two hundred and fifty-seven women were studied: 64 non-b-thalassemic, non-pregnant women made up the reference group, 89 were non-b-thalassemic pregnant women, and 104 were b-thalassemic pregnant or non-pregnant women. The full blood count, hemoglobin levels and iron status (serum iron and serum ferritin levels) were explored by traditional methods. Serum Epo and STFR levels were measured with standard commercial kits. RESULTS: In non-b-thalassemic women the mean non-pregnant Epo level (10.95 +/-4. 7 mU/mL) increased in the first trimester (17.12 +/-5.18 mU/mL), was stationary in the second, and increased again in the third (31. 43+/-14.13 mU/mL). STFR mean value dropped in early pregnancy from 2. 40+/-0.72 mg/L to 1.78 +/- 0.64 mg/L, and then returned to the original value (2.38 +/- 0.94 mg/L). In b-thalassemic women the mean non-pregnant Epo level (15.00 +/-6.56 mU/mL) was higher than in non-thal non-pregnant women. During pregnancy it progressively increased to 35.60+/-25.46 mU/mL. STFR (non-pregnant level 3.37+/-1. 07 mg/L) gradually increased throughout the whole gestation period and by the third trimester its level was markedly higher than that of non-b-thal women at the corresponding stage of gestation (9. 41+/-5.39 mg/L vs 2.40+/-0.72 mg/L). INTERPRETATION AND CONCLUSIONS: The STFR level changed to different extents in non-b-thal and b-thal women during their pregnancies. In the former STFR markedly decreased in early pregnancy; in the latter it showed no decrease in the first trimester, increased in the second and reached very high values in the third. This time course is likely to be the consequence of erythroid bone marrow hyperplasia and hyperactivity, which are usually present in all b-thalassemic patients and in heterozygous carriers as well.